2015
DOI: 10.1007/s00268-015-2981-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Partial Sleeve Gastrectomy with Fundoplication for Gastroesophageal Reflux and Delayed Gastric Emptying

Abstract: With careful patient selection and work-up, SG and HH repair with fundoplication may improve quality of life by coupling adequate reflux control with improved gastric emptying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…In this context, in order to avoid the mentioned complications, there are previous studies suggesting combinations of antireflux surgery with sleeve gastrectomy. In addition, some authors have proposed some technical modifications in order to improve postoperative results 9 , 11 , 20 , 21 , 22 , 34 , 35 , 36 , 40 . Haswalli et al 16 recommended hiatoplasty and anterior fundoplication to treat gastroesophageal reflux using a dilated fundus after LSG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, in order to avoid the mentioned complications, there are previous studies suggesting combinations of antireflux surgery with sleeve gastrectomy. In addition, some authors have proposed some technical modifications in order to improve postoperative results 9 , 11 , 20 , 21 , 22 , 34 , 35 , 36 , 40 . Haswalli et al 16 recommended hiatoplasty and anterior fundoplication to treat gastroesophageal reflux using a dilated fundus after LSG.…”
Section: Discussionmentioning
confidence: 99%
“…Haswalli et al 16 recommended hiatoplasty and anterior fundoplication to treat gastroesophageal reflux using a dilated fundus after LSG. Le Page et al 20 presented the effects of a sleeve gastrectomy associated with fundoplication in patients with symptoms of reflux and delayed gastric emptying. The study included four patients who also had hiatal hernia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering all these findings, several bariatric teams proposed a modification to the usual surgical technique of LSG by adding a different fundoplication-Table 1 [11][12][13][14][15][16][17][18]. The intents of these techniques were to minimize the rate of postoperative GERD, to protect the staple line of the angle of His, and finally, to provide a safe and effective alternative for patients with contraindication to LRYGB because of GERD.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed mechanisms include a change in gastric distensibility by reducing gastric volume and altered contractility by resetting the gastric pacemaker. Since 2013, several case studies reported on single-center efficacy of gastric surgery in refractory gastroparesis [13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Up to the present, randomized studies on the overall efficacy and safety of surgery for gastroparesis are lacking.…”
mentioning
confidence: 99%